2020
DOI: 10.14744/ijmb.2020.96268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum proinflammatory cytokines, oxidative stress and some other biochemical markers in chronic viral hepatitis B and C infections

Abstract: Evaluation of serum proinflammatory cytokines, oxidative stress, and other biochemical markers in chronic viral hepatitis B and C infections H epatitis B virus (HBV) and hepatitis C virus (HCV) infections are a global health problem that is endemic in Turkey. These viruses attack the liver and can cause both acute and chronic hepatitis infection [1, 2]. Chronic hepatitis infection presents a major risk for the development of hepatocellular carcinoma [2, 3. 4]. These viruses directly induce oxidative stress Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In the current study, the levels of zinc were highly significantly lower whereas the levels of copper were highly significantly higher in the patient groups than in the control group. These findings back up a prior study conducted in Turkey, which found that chronic infection of viral hepatitis affects Zn and Cu homeostasis, resulting in an elevation in serum copper levels and a reduction in zinc levels [39]. Zinc deficiency has been noticed in many types of hepatic disease, including viral hepatitis.…”
Section: Distribution Of Serum Zinc Copper and Iron Concentrations (µ...supporting
confidence: 75%
“…In the current study, the levels of zinc were highly significantly lower whereas the levels of copper were highly significantly higher in the patient groups than in the control group. These findings back up a prior study conducted in Turkey, which found that chronic infection of viral hepatitis affects Zn and Cu homeostasis, resulting in an elevation in serum copper levels and a reduction in zinc levels [39]. Zinc deficiency has been noticed in many types of hepatic disease, including viral hepatitis.…”
Section: Distribution Of Serum Zinc Copper and Iron Concentrations (µ...supporting
confidence: 75%